Comparing Ultralong Carbon Nanotube Growth from Methane over Mono- and Bi-Metallic Iron Chloride Catalysts - Tim Yick (Nanomaterials, 2023)
This research endeavours to study the growth of ultralong carbon nanotubes (UL-CNTs) from methane using diverse catalysts, namely FeCl3, bi-metallic Fe-Cu, Fe-Ni, and Fe-Co chlorides. Aqueous catalyst solutions were evenly dispersed on silica substrates and grown at 950 °C in the presence of hydrogen via a horizontal chemical vapour deposition (CVD) furnace. The samples underwent characterisation by Raman spectroscopy, scanning electron microscopy (SEM), and optical microscopy to identify the quality of CNTs and enumerate individual UL-CNTs. Our findings revealed that FeCl3, as a mono-metallic catalyst, generated the longest UL-CNTs, which measured 1.32 cm, followed by Fe-Cu (0.85 cm), Fe-Co (0.7 cm), and Fe-Ni (0.6 cm), respectively. The G/D ratio (graphene to defects) from the Raman spectroscopy was the highest with the FeCl3 catalyst (3.09), followed by Fe-Cu (2.79), Fe-Co catalyst (2.13), and Fe-Ni (2.52). It indicates that the mono-iron-based catalyst also produces the highest purity CNTs. Moreover, this study scrutinises the vapour-liquid-solid (VLS) model for CNT growth and the impact of carbide formation as a precursor to CNT growth. Our research findings indicate that forming iron carbide (Fe3C) is a crucial transition phase for amorphous carbon transformation to CNTs. Notably, the iron catalyst generated the longest and densest CNTs relative to other iron-based bi-metallic catalysts, which is consistent with the temperature of carbide formation in the mono-metallic system. From correlations made using the phase diagram with carbon, we conclude that CNT growth is favoured because of increased carbon solubility within the mono-metallic catalyst compared to the bi-metallic catalysts.